Economic Process and Entrepreneurship - Rezaei Mirghaed, Mohsen (Journal of Entrepreneurship, Business and Economics; Vol 3 No 2 (2015), 2015)
There is a robust body of knowledge around the theory of Entrepreneurship, but the lack of a compre-hensive and widely accepted view to describe this phenomenon is obvious. There is two main streams in entrepreneurship literature, first the Schumpeterian view which emphasizes on ideas, innovation and creativity and second view, known as Kirznerian point that views opportunities of market as the core of entrepreneurship .This conflict can be easily understood from Kirzner‟s words that says” Schumpeter‟s entrepreneur, I pointed out, was essentially disruptive, destroying the pre-existing state of equilibrium. Entrepreneur, on the other hand, was responsible for the tendency through which ini-tial conditions of disequilibrium come systematically to be displaced by equilibrative market competi-tion”, which are paradoxical to some extent. In this paper, author believes that there can be issued a new conceptual framework about the entrepreneurship. This framework views entrepreneurship in an economic, product-transaction-based process. The value of entrepreneurial activities is arisen from mutual interests of human beings, which is the neglected part of Schumpeter and Kirzner‟s views to the phenomenon Entrepreneurship. Conceptual paper Reference to this paper should be made as follows: Rezaei Mirghaed, M. (2015). “Economic Process and Entrepreneurship”, Journal of Entrepreneurship, Business and Economics, Vol. 3, No. 2, pp. 86–109.